Interculturalidade na educa????o brasileira: a inser????o de bolivianos em escolas p??blicas paulistanas - Gon??alves, Ana L??cia Novais (2014)
This paper presents a brief historical overview of Bolivian immigration to Brazil, analyzes the inclusion of these public schools in S??o Paulo, as well as the looks of managers and teachers for this clientele, comprising four schools of the capital with many of these students, as well as understands the prospects of these immigrants on education, work and cultural events. Therefore, we use as theoretical framework Paulo Freire and his propositions about an egalitarian, intercultural education that prizes appreciation of the subject in order to understand the ???Pedagogy of the Oppressed??? in their oppressor-oppressed relationship, this perspective also analyzing prejudice and discrimination committed by Brazilian compatriots and, besides the great difficulty in understanding the language (Portuguese).